OP0156 Methotrexate increases expression of the cell cycle regulators lbh and p21 and reduces fibroblast-like synoviocyte proliferation after mitogen stimulation. (15th June 2017) - Bergström, B; Carlsten, H; Ekwall, A-KH
Abstract : Background: Activated fibroblast-like synoviocytes (FLS) are key effector cells in the joint in rheumatoid arthritis (RA). Local FLS proliferation is responsible for synovial hyperplasia, a key feature of the RA synovium correlating with disease activity. PDGF and IL-1b are known FLS mitogens. LBH is a transcription regulator and tumor suppressor, recently identified as a RA risk gene. We have demonstrated that LBH regulates FLS proliferation and that LBH expression is regulated by growth factors and by epigenetic mechanisms[1]. Methotrexate (MTX) is still the first-line treatment of RA but the target cells and mechanism of action of the low dose used in rheumatic diseases is largely unknown. Increased expression of cell cycle checkpoint genes[2] and modified DNA methylation[3] in immune cells have recently been described. Objectives: The aim of this study was to investigate the effects of MTX on PDGF and IL1b-induced FLS proliferation in vitro and in particular on the expression of LBH, cell cycle genes (CDKN1A/p21 and CCND1/cyclinD1) and on genes regulating DNA methylation (DNMTs) in order to further understand the pharmacodynamics of this drug in RA and to identify novel markers for drug response. Methods: Primary FLS from RA patients and from patients with osteoarthritis (OA) were plated on day 0 in DMEM complete, pre-treated 24 hours with MTX or control medium day 1, and stimulated with 20ng/ml PDGF+2 ng/ml IL-1b with or without 1 uM MTX in DMEM with 1% FBS for 24–48 hours starting day 2. Cells were then harvested for qPCR for gene expression and flowcytometry for cell cycle analysis. Results: Stimulating RA-FLS cultures (n=3) with PDGF+IL-1b for 24 hours, pushed 24, 5±3, 5% cells into G2/M phase compared to 3, 4±0, 8% in unstimulated controls. Interestingly, treating PDGF+IL1b stimulated FLS with MTX, significantly inhibited cell cycle progression (4, 6±1, 9% in G2/M phase, p= 0, 02). PDGF+IL-1b stimulation of FLS for 24 hours reduced LBH mRNA expression. However, in the presence of 1uM MTX the LBH mRNA expression was significantly higher in RA-FLS (3, 2±0, 5 fold, p= 0.002, n=5) and in OA-FLS (2, 2±0, 5 fold, p= 0, 02, n=5) after PDGF+IL-1b stimulation compared to untreated controls. In addition, MTX treatment strikingly increased the CDKN1A expression 14, 3±4, 4 fold ( p= 0, 006) of treated vs untreated stimulated FLS. Furthermore, we found that 1 uM MTX restored and increased a lowered DNMT1 mRNA expression to 144±12% after PDGF+IL1b stimulation. There were no significant effects of MTX on CCND1 or DNMT3a expression at investigated time points. Conclusions: Therapeutic doses of MTX reduce mitogen induced FLS proliferation and significantly revert mitogen-induced reduction of LBH and p21 expression in RA FLS. MTX restores expression of DNMT1 suggesting that MTX might regulate gene expression and proliferation by affecting the epigenome. References: Ekwall, A.K., et al., The Rheumatoid Arthritis Risk Gene LBH Regulates Growth in Fibroblast-like Synoviocytes. Arthritis Rheumatol, 2015. 67(5): p. 1193–202. Spurlock, C.F., 3rd, et al., Methotrexate increases expression of cell cycle checkpoint genes via JNK activation. Arthritis Rheum, 2012. 64(6): p. 1780–9. Cribbs, A.P., et al., Methotrexate Restores Regulatory T Cell Function Through Demethylation of the FoxP3 Upstream Enhancer in Patients With Rheumatoid Arthritis. Arthritis Rheumatol, 2015. 67(5): p. 1182–92. Disclosure of Interest: None declared